Surgical Management of Inflammatory Eye Disease - Becker, Matthias D.; Davis, Janet (Springer Berlin Heidelberg, 2008)
Ocular inflammation presents a broad spectrum of clinical manifestations. Inflammatory activity can often be managed by drug therapy. However, inadequate medical therapy may permit the development of various complications in the eye that cannot be sufficiently treated pharmacologically. Whereas drug management demands an interdisciplinary approach with well-trained specialists, surgical treatment of ocular complications due to inflammation requires an experienced surgeon. This book offers evidence-based information and a step-by-step guide on all relevant surgical procedures, which is otherwise rare to find. Internationally renowned experts in the field provide answers to questions such as: What is the spectrum of clinical manifestations of inflammatory complications? When is medical therapy no longer helpful? What are the absolute, relative indications, and contraindications for defined surgical procedures in this field? What are the preferred surgical instruments and machines for these procedures? How can postoperative complications be avoided? How can drugs support the success of a surgical procedure? An accompanying DVD describes every step of the classic surgical procedures, the management of intraoperative complications, and special situations.
Includes bibliographical references and index
Keywords: Aufsatzsammlung; Chirurgie; Augenentzündung